2021
DOI: 10.3389/fimmu.2021.627435
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Sepsis Exacerbates CD4+ T Cell Exhaustion and Decreases Antiviral Immune Responses

Abstract: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to an infection. It is a disease with a high incidence, mortality, and recurrence rate and frequently results in its survivors requiring readmission into hospitals. The readmission is mainly due to recurrent sepsis. Patients with recurrent sepsis are more susceptible to secondary infections partly due to immune dysfunction, leading to a higher mortality in the long term. However, there remains a gap in the understanding of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Research on the epidemiology, prevention, and management of sepsis is an important topic for critical care medicine, surgery, and anesthesiology, where clarification of the complex pathophysiological mechanism of sepsis is a fundamental problem (14,23,24). Since 1992, the definitions of sepsis, severe sepsis, and septic shock, as well as associated clinical and laboratory studies have relied on the presence of infection and the characteristics of systemic inflammatory response syndrome (SIRS) (1,(24)(25)(26)(27)(28).…”
Section: Sepsismentioning
confidence: 99%
See 4 more Smart Citations
“…Research on the epidemiology, prevention, and management of sepsis is an important topic for critical care medicine, surgery, and anesthesiology, where clarification of the complex pathophysiological mechanism of sepsis is a fundamental problem (14,23,24). Since 1992, the definitions of sepsis, severe sepsis, and septic shock, as well as associated clinical and laboratory studies have relied on the presence of infection and the characteristics of systemic inflammatory response syndrome (SIRS) (1,(24)(25)(26)(27)(28).…”
Section: Sepsismentioning
confidence: 99%
“…Compelling experimental and clinical evidence has indicated that sepsis is a multi-dimensional heterogeneous syndrome, which is reflected in the host's variable immune responses (23,135,136). (40,76,80); therefore, these studies do not fully reflect the heterogeneous characteristics of sepsis (91,135).…”
Section: Host-dependent Treg Patterns In Sepsismentioning
confidence: 99%
See 3 more Smart Citations